Parents' Role, Learning Motivati PENGARUH PERAN ORANG TUA TERHADAP MOTIVASI DAN KEDISIPLINAN BELAJAR ANAK SEBAGAI DAMPAK WABAH COVID-19 - DESIKA PUTRI MARDIANI (Jurnal Paradigma, 2021)
This research aims to analyze the influence of the role of parents on learning motivation and learning discipline of children as a result of the Covid-19 outbreak and explain how much influence this has. The location of this research is the Islamic Education Institute of Kindergarten Al-Ishlah Ngale, Ngawi Regency by taking a sample of 74 people. This research uses quantitative research methods and data collection techniques in the form of questionnaires, interviews and documentation. Assessment of the questionnaire is using a Likert scale and presenting the data using an interval scale, while data processing uses the SPSS version 25 software. The results of data processing show that Ho is rejected and Ha is accepted, with the regression test results obtained by the F test value of 4.319> F table 3.97 for variable X to Y1 and F value of 7.168> F table 3.97 for regression test of variable X against Y2. Taking into account the significance value of both <0.05, it is concluded that there is a significant influence between the role of parents and children's learning motivation and children's learning discipline. This conclusion is supported by the results of the T test with a value of 2.078 and 0.09 which are> 1.993 T table. Furthermore, the value of R square for variable X on Y1 is 0.57 illustrating the magnitude of the influence of the role of parents on children's learning motivation is 57% and the value of R square is 0.91 for variable X on Y2 illustrates the large influence of the role of parents on children's learning discipline. by 91%. The direction of this research is positive, indicated by the regression equation ? = 29.571 + 0.252X and ? = 22.230 + 0.251X. Thus, the higher the role of parents, the more children's motivation and discipline will increase.